Guru Kristen sebagai Pembimbing dan Penuntun dalam Konsep Kelas Tiga Dinding Ki Hajar Dewantara Melalui Pembelajaran Autentik [The Christian Teacher as Mentor and Guide in Ki Hajar Dewantara's Third Wall Classroom Concept Through Authentic Learning] - Sihombing, Sarali; Rahmadi, Pitaya (Universitas Pelita Harapan, 2024)
The Christian teacher as guide and mentor is not focused on academic achievement only, but rather guides and assists students to become like Christ and responsible individuals. However, the reality is that many teachers still adopt traditional learning, neglect other skills, and distance themselves from Biblical truth. This article presents the role of the Christian teacher as a guide and mentor in the context of the relevance of science to the environment, especially Ki Hajar Dewantara's